Systemic lupus of pediatric onset in Afro-Caribbean children: a cohort study in the French West Indies and French Guiana - Arthur Felix; Frederique Delion; Benoit Suzon; Elise Martin; Anais Ogrizek; M'hamed Mohamed Sahnoun; Claudia Hospice; Aurelie Armougon; Emma Cuadro; Narcisse Elenga; Moustapha Dramé; Brigitte Bader-Meunier; et al. (BMC, 2022)
Abstract Background Systemic diseases of pediatric onset are more frequent in the Afro-Caribbean population. We performed a study of patients followed in the French overseas departments of America (FOAD) for pediatric systemic lupus erythematosus (pSLE). The aims were to describe the clinical and biological specificities during childhood in this population. Methods A retrospective study was conducted between January 2000 and September 2021. Patients with pSLE were identified from multiple sources: computerized hospital archives, registry of referring pediatricians, adult specialists in internal medicine and the French National Registry for rare diseases. We studied SLE with pediatric onset defined by international criteria. Results Overall, 2148 patients were identified, of whom 54 were included. The average follow-up was 8.3 years (range: 0.3-25 years). We observed an increase in new diagnoses over time. At onset, pSLE patients had a median of 10 SLICC criteria (range: 4-12), and the median EULAR/ACR 2019 score was 38 (12-54). At onset, one third of patients had renal involvement, 15% had neurolupus and 41% cardiac involvement. During childhood, 54% had renal involvement, and 26% suffered from neurolupus. Patients suffered a median of 3 flares during childhood, and 26% had more than 5 flares. Patients with younger age at onset had worse outcomes than those who were older at diagnosis, i.e., more flares (median 5, p = 0.02) and requiring an average of 4 background therapies (p = 0.04). Conclusion The outcomes of Afro-Caribbean patients were similar to those in Western population, but with worse disease activity at onset. Further studies should be performed to identify the genetic and environmental factors in this population.